Phytochemical Characterization of Terminalia catappa Linn. Extracts and Their antifungal Activities against Candida spp. - Terças, Analucia G.; Monteiro, Andrea de Souza; Moffa, Eduardo B.; Santos, Julliana R. A. dos; Sousa, Eduardo M. de; Pinto, Anna R. B.; Costa, Paola C. da Silva; Borges, Antonio C. R.; Torres, Luce M. B.; Barros Filho, Allan K. D.; Fernandes, Elizabeth S.; Monteiro, Cristina de Andrade (Frontiers in Microbiology, 2017)
Terminalia catappa Linn bark is used to treat dysentery by various populations in Southeast Asian countries, and its leaves have also been used in traditional medicine to treat hepatitis in India and the Philippines. Here, the antifungal actions of crude hydro-alcoholic extract (TcHE) and fractions from T. catappa leaves were assessed via the agar diffusion and microdilution tests on Candida reference strains and clinical isolates from patients with acquired immunodeficiency syndrome (AIDS). Additionally, the potential cytotoxic effects of TcHE were assessed on cultured human peripheral blood mononuclear cells (PBMC). T. catappa fractions and sub-fractions were analyzed by gas chromatography coupled to mass spectrometry with electron impact (GC/MS/EI), high-performance liquid chromatography coupled to mass spectrometry "electrospray" ionization in positive mode (HPLC/MS/MS/ESI+) and hydrogen nuclear magnetic resonance (1HNMR). TcHE and its fractions were able to inhibit the growth of all tested Candida strains with the n-butanol (FBuOH) fraction presenting the best antifungal activity. Testing of different FBuOH sub-fractions (SF) showed that SF10 was the most active against Candida spp. Fractioning of SF10 demonstrated that 5 out of its 15 sub-fractions were active against Candida spp., with SF10.5 presenting the highest activity. Chemical analysis of SF10 detected hydrolysable tannins (punicalin, punicalagin), gallic acid and flavonoid C-glycosides. Overall, the results showed that T. catappa L. leaf extract, fractions and sub-fractions were antifungal against Candida spp. and may be useful to treat diseases caused by this fungus.